The effects of increasing rates of HIV/AIDS-related illness and death on rural families in Zombia district, Malawi: A longitudinal study - Peters, Pauline E.; Kambewa, Daimon; Walker, Peter (International Food Policy Research Institute, 2008)
The research, conducted from January to December 2006, investigated the effects of the HIV epidemic on a Zomba District sample of households that has been studied since 1986. The sample families follow matrilineal and matrilocal patterns of organization: descent and inheritance are traced through the mother’s line, and husbands move to their wives’ village on marriage. Land is inherited by female heirs and sons are expected to use their wives’ land. The research used multiple methods - ethnography and questionnaire surveys. Results included that 50% of the sample households had had at least one death due (certainly to likely) to HIV/AIDS; and 29% were taking care of orphans during 2006. A central conclusion is that the matrilineal family continues to be the major, frequently sole, support to bereaved households. Without the mobilizing power of the matrilineal family, there would be far more homeless orphans, and far more acutely distressed individual persons and households. That the extended matrilineal family is able in most cases, so far, to absorb most of the very high costs, material and otherwise, of the epidemic should not be assumed to be ‘the’ case for all of Malawi, still less for Africa. Many extended matrilineal families are already very stretched, and, in light of the increasing numbers of sick and dying people, without improvements in the services to help them increase their income level, their capacity to care for the increasing numbers of sick and of orphans, and to gain more equitable access to medical care, some may find it difficult to maintain their roles as primary caretakers.